Non-Powder gunshot injury of the parapharynx space - Raden Ayu Hardianti Saputri; Annika Famiasti; Nur Akbar Aroeman; Agung Dinasti Permana; Sinta Sari Ratunanda (PERHATI-KL, 2021)
ABSTRACTBackground: Non-powder firearm is a weapon which used compressed air or CO2 gas to propel lead or steel ball pellets. Trauma caused by non-powder firearm has the potential for significant morbidity and mortality. Head and neck wounds account for 13.8%-30% of all non-powder firearm injuries. Bullets from gunshots often nest in the parapharyngeal space. Purpose: To present a case of non-powder firearm trauma in parapharyngeal space and its management. Case Report: A 13 years-old boy came with non-powder firearm trauma on the left cheek and bleeding from the left nostril. Upon physical examination there was a vulnus sclopetorum sized 0.5x0.5 cm without active bleeding in the left zygoma area. Three dimensional CTscan showed a hyperdense metal lesion in the left parapharyngeal space with 42.6 cm distance from penetrating site to the bullet location. The bullet was then extracted with transparotid approach surgery guided by C-arm imaging. Clinical Question: How is the management of trauma from a non-powder gunshot in the parapharyngeal space? Review method: Literature search through Pubmed, Cochrane Library, and Wiley using non-powder firearm injury in parapharyngeal space and its management as keywords. Result: The search obtained 11 articles. Based on inclusion and exclusion criteria, one article was found relevant with the topic i.e. one case report of non-powder firearm injury in parapharyngeal space and its surgical management. Conclusion: The safe procedure for retrieving bullets from the parapharyngeal space is in the form of surgery with the help of C-arm imaging to pinpoint the bullet’s location and to prevent further complication.Keywords: non-powder firearm, gunshot injury, parapharynx space, C-armABSTRAKLatar belakang: Senapan angin merupakan senjata yang menggunakan tenaga penggerak berjenis gas CO2 untuk melontarkan peluru. Trauma akibat senapan angin dapat berpotensi fatal. Sebanyak 13,8-30% luka tembak senapan angin terjadi pada daerah kepala dan leher. Salah satu ruang leher yang kerap menjadi tempat bersarangnya peluru adalah ruang parafaring. Tujuan: Melaporkan kasus dan penanganan trauma tembak senapan angin pada parafaring. Laporan kasus: Anak laki-laki berusia 13 tahun dengan riwayat tertembak senapan angin di pipi kiri dan perdarahan dari hidung kiri. Pada pemeriksaan fisis didapatkan vulnus sklopetorum berukuran 0,5 x 0,5 cm tanpa perdarahan aktif di area zigoma kiri. Hasil CT scan 3D didapatkan lesi hiperdens dengan densitas metal pada parafaring kiri, berjarak 42,6 mm dari luka. Benda asing peluru kemudian diekstraksi melalui tindakan operatif menggunakan pendekatan transparotid dengan bantuan C-Arm. Pertanyaan klinis: Bagaimana penatalaksanaan trauma tembak senapan angin pada ruang parafaring? Telaah literatur: Penelusuran literatur melalui Pubmed, Cochrane Library, dan Wiley menggunakan kata kunci luka tembak senapan angin pada ruang parafaring dan penatalaksanaannya. Ditemukan 11 artikel, dan pemilihan artikel berdasarkan kriteria inklusi dan eksklusi, terdapat satu penelitian yang relevan. Hasil: Didapat satu laporan kasus tentang luka tembak senapan angin di ruang parafaring dengan tindakan bedah sebagai penanganannya. Kesimpulan: Tatalaksana pengambilan peluru yang aman adalah dengan pendekatan pembedahan dengan bantuan C-Arm untuk mencegah komplikasi lebih lanjut.Kata kunci: senapan angin, luka tembak, trauma, ruang parapfaring, C-arm